Thromboprophylaxis with antithrombin gamma and unfractionated heparin for a pregnant woman complicated by hereditary antithrombin deficiency. Issue 2 (27th October 2019) - Hisano, Michi; Mitsui, Mari; Sago, Haruhiko; Yamaguchi, Koushi
Abstract : Antithrombin replacement using recombinant human antithrombin (antithrombin gamma) is a well‐tolerated treatment and effective as thromboprophylaxis for a pregnant woman with hereditary antithrombin deficiency.